(untitled) - Ehab Saad Elkhayat (Faculty of Pharmacy, Cairo University, 2016)
Chemical investigation of the cytotoxic n-hexane fraction of the rhizomes of Gazania linearis (Thunb.) Druce (Asteraceae), led to isolation of a steroid-glucoside and three triterpenes, together with three sesquiterpene lactones. The chemical structures of the isolated compounds were established based on their spectroscopic analyses (IR, 1D and 2D NMR, and mass spectroscopy) to be: lupeol-3-O-stearate (1), costunolide (2), 11,13-dihydro-costunolide (3), santamarine (4), in addition to lupeol (5), β-amyrin (6), and β-sitosterol-3-O-β-d-glucopyranoside (7). The n-hexane fraction and compounds 4 and 6 displayed moderate cytotoxic activity toward MCF-7 and COLO-205 with IC50 values of 24.3, 34.0 μg/mL and 53.25 μM and 61.27, 21.10, and 25.70 μM, respectively compared to doxorubicin (IC50 0.11 and 0.44 μM, respectively).